DEVELOPMENT OF TEACHING MODULES FOR DIFFERENTIATED LEARNING IN THE INDEPENDENT CURRICULUM FOR ELEMENTARY SCHOOL TEACHERS IN KUPANG CITY - Rista Apriliya Devi; Kurniayu Triastuti R. A. Ratu; Sumardi W. Ndolu; Gupuh Rahayu; Nadia Khairun Nisa (Journal of Community Research and Engagement, 2024)
This Community Service aims to provide in-depth insight into the principles of the Merdeka Curriculum, as well as provide practical skills to teachers in designing and delivering learning that can be tailored to the needs and abilities of each student so that they are able to compile Differentiated Learning teaching modules. This training took place at SD Inpres Lasiana, Kupang City. There were 24 participants, who were representatives from schools in Kupang City. The methods used in this activity were discussion, question and answer, assignment, simulation and demonstration. The result of this activity is that teachers are able to develop differentiated learning designs (Differentiated Teaching Modules) and demonstrate these designs. Through this activity, teachers gain direct experience related to the implementation of differentiated learning in strengthening the implementation of the independent curriculum in elementary schools. Keywords: Teaching Module, Differentiated Learning, Independent Curriculum